A construção do processo de imaginação e criação no brincar com sucata: a experiência com crianças de dois anos a dois anos e três meses - Silva, Márcia Tostes Costa da (2017)
The present research investigates how a child builds their imagination and creation process by playing with scrap material in the nursery environment. An action-research was developed from a qualitative approach in a day care center located in Carapicuíba, a city in São Paulo, Brazil. The project acted with nine children, boys and girls, aged between two and two years and three months. It was possible to verify that the child enhances imagination and creation process when he or she explores scrap materials in different ways, re-signifying them. However, the process of expanding creation and imagination will not occur only by the material itself, it needs organization in spaces. The reference scholars for this project were Philippe Ariès (1981), Loris Malaguzzi (1999), Tizuko Morchida Kishimoto (1998, 2010ab), Gilles Brougère (2008), Luise Weiss (1989), Lev Vygotsky (2007, 2009), Aldo Fortunati (2009), Jens Qvortrup (2011), Ana Lúcia Goulart Faria (1999), Daniel B. Elkonin (2009) e Michel Thiollent (2009).